OPINIONS OF SECOND GRADE ELEMENTARY SCHOOL STUDENTS ABOUT FOREIGN LANGUAGE TEACHING BY NATIVE SPEAKER INSTRUCTORS - Iiguzela, Bahar; Kirmizi, Bulent (Pegem Akad Yayincilik Egitim Danismanlik Hizmetleri Tic Ltd Sti, 2013)
The objective of this study was to determine the opinions of secondary school students regarding the native speaker instructors in the foreign language lesson. The study was conducted in a private secondary school in which especially American and German native speaker instructors' lecture in the foreign language classes. Voluntarily participated in this study 45 students who were attending the sixth and seventh grades in that school. In this study, quantitative and qualitative research approaches were used. The data were collected in the academic year 2009-2010. The quantitative data was collected with a survey that included 12 items which was developed by the researchers of this study. In the qualitative part, an open-ended question was asked to the participants to understand their attitudes towards the native speaker instructors. The results of this study indicated that most of the sixth and seventh grade students of this secondary school have negative attitude to the native speaker instructors in their foreign language lesson. The students stated that their desire to learn a foreign language had decayed in the native speaker instructors classes. Suggestions were made to make teaching-learning process more efficient, effective and live up to student's expectations.
Keywords: Foreign language teaching; native speaker instructors; secondary school; anxiety